Wheat floret survival as related to pre-anthesis spike growth - González, Fernanda Gabriela (2011)
Further improvements to wheat yield potential will be essential to meet future food demand. As yield is related to the number of fertile florets and grains, an understanding of the basis of their generation is instrumental to raising yield. Based on (i) a strong positive association between the number of fertile florets or grains and spike dry weight at anthesis; and (ii) the finding that floret death occurs when spikes grow at maximum rate, it was always assumed that floret survival depends on the growth of the spike. However, this assumption was recently questioned, suggesting that assimilates diverted to the spike do not determine the number of florets and grains and that the onset of floret death may instead be a developmental process that is not associated with spike growth. In this study, the relationships between the fate of floret primordia and spike growth from six independent experiments that included different growing conditions (greenhouse/field experiments, growing seasons, photoperiod/shading treatments during the floret primordia phase) and diverse cultivar types (winter/spring, semi-dwarf/standard-height, photoperiod sensitive/insensitive) were re-analysed together. Onset of floret death was associated with the beginning of spike growth at the maximum rate in c. 80% of the cases analysed; and the rate of floret death (the main determinant of floret survival) showed a negative quantitative relationship with spike weight at anthesis. As floret death and survival were shown to be linked to pre-anthesis spike growth, the strategy of focusing on traits associated with pre-anthesis spike growth when breeding to increase wheat yield potential further is valuable.